Leveraging Intellectual Capital through Dynamic Capabilities for Sustainable Competitive Advantage - Angelia Nirwana Sari, Laras; Setiawati, Liya (Inovasi Analisis Data, 2025)
Purpose: The purpose of this study is to identify the impact on long-run competitive advantage due to intellectual capital and the direct and moderating effect of dynamic capabilities in an integrated strategic management model. Method: The paper is quantitative using secondary panel data and adopts partial least squares structural equation modeling to test the posited relationships. Intellectual capital is proxied by value-based measures, long-term competitive advantage is represented in by financial and market based performance measures, and dynamic capabilities are operationalized using investment intensity in R&D-oriented innovation. Measurement model confirmation, structural model evaluation and moderation testing are the highlights of empirical analyses. Findings: The findings indicate that intellectual capital has a positive & significant effect on long-term competitive advantage. Dynamic capabilities also exhibit a significant direct effect on the long-term competitive advantage. Furthermore, dynamic capabilities positively moderate the relationship between IC and firm-based long-term competitive advantage, suggesting that firms with higher ability to sense and seize opportunities are more adept at transforming resource-based knowledge into competitive gains. Novelty: This research offers fresh empirical evidence by incorporating intellectual capital and dynamic capabilities into an integrated model of long-term competitive advantage, and emphasizing the contingent influence of dynamic capabilities to enhance strategic value of intellectual capital. Implications: The results have significant implications for strategists by highlighting the necessity for companies to develop both intellectual capital and dynamic capabilities altogether in order to secure sustainable competitive advantage within dynamic environments.